Odpowiedź :
Odpowiedź:
Szczegółowe wyjaśnienie:
x-2 /3+y=1/*3
x-2/ 6+3y= -2 /*6
x-2+3y=3
x-2+18y= -12
x+3y=5 /*(-1)
x+18y=-10
-x-3y=-5
x+18y= -10
+
15y=-15/:15
y= -1
x+3*(-1)=5
x-3=5
x=8
[tex]\begin{cases} \frac{x-2}{3} +y=1\ \ |*3 \\ \frac{x-2 }{6} + 3y=-2\ \ |*6\end{cases}\\\\ \begin{cases} x-2+3y=3\\ x-2+18y=-12\end{cases} \\\\ \begin{cases} x +3y=3+2\\ x +18y=-12+2\end{cases}\\\\ \begin{cases} x +3y=5\ \ |*(-1)\\ x +18y=-10\end{cases}\\\\ \begin{cases} -x -3y=-5\\ x +18y=-10\end{cases}\\---------\\15y=-15\ \ |:15\\y=-1\\\\\\x+3y=5\\\\x=5-3y\\\\x=5-3*(-1)=5+3=8\\\\\begin{cases} x=8\\ y=-1\end{cases}[/tex]